A case of gastric aberrant pancreas with bleeding and diagnosed by endoscopic ultrasonography - Tagata, T. (Endosc Ultrasound, 2014)
Aberrant pancreas is used to describe ectopic pancreatic tissue lying outside its normal location with no anatomic or vascular connection to the pancreas proper. Patients with aberrant pancreas are usually asymptomatic, so aberrant pancreas are typically discovered incidentally during endoscopy, surgery, or autopsy. This time, we report a case of gastric aberrant pancreas bleeding was repeated and endoscopic hemostasis was difficult. A 22-year-old man was admitted to a hospital with a complaint of epigastric pain and melena. Upper gastrointestinal endoscopy and endoscopic ultrasonography (EUS) revealed a submucosal tumor with a bleeding ulcer at the anterior wall of the antrum in the stomach, and diagnosed it as an aberrant pancreas. It was hard to stop bleeding by in total 7 times endoscopic hemostasis and anemia was gradually progressed, so partial gastrectomy was performed. This gastric tumor measured 40 mm × 30 mm × 20 mm and had a severe ulcerative change. The pathological diagnosis was aberrant pancreas with Langerhans islet, acinous cells and excretory duct. (Heinrich type) Until December 2013 in Japan, 13 cases of gastric aberrant pancreas with bleeding have been reported and in these, a surgery was done in 11 cases. In gastric aberrant pancreas cases with ulcer formation like this case, endoscopic hemostasis is expected to be difficult, and surgery is necessary. Hence, early accurate diagnosis by EUS is a very important to decide better treatment plan.